Live cell imaging of viral entry - Sun, Eileen (Elsevier, 2013)
Viral entry encompasses the initial steps of infection starting from virion host cell attachment to viral genome release. Given the dynamic interactions between the virus and the host, many questions related to viral entry can be directly addressed by live cell imaging. Recent advances in fluorescent labeling of viral and cellular components, fluorescence microscopy with high sensitivity and spatiotemporal resolution, and image analysis enabled studies of a broad spectrum across many viral entry steps, including virus-receptor interactions, internalization, intracellular transport, genomic release, nuclear transport, and cell-to-cell transmission. Collectively, these live cell imaging studies have not only enriched our understandings of the viral entry mechanisms, but also provided novel insights into basic cellular biology processes.